A nonS-locus F-box gene breaks self-incompatibility in diploid potatoes - Ma, Ling (Nat Commun, 2021)
Potato is the third most important staple food crop. To address challenges associated with global food security, a hybrid potato breeding system, aimed at converting potato from a tuber-propagated tetraploid crop into a seed-propagated diploid crop through crossing inbred lines, is under development. However, given that most diploid potatoes are self-incompatible, this represents a major obstacle which needs to be addressed in order to develop inbred lines. Here, we report on a self-compatible diploid potato, RH89-039-16 (RH), which can efficiently induce a mating transition from self-incompatibility to self-compatibility, when crossed to self-incompatible lines. We identify the S-locusinhibitor (Sli) gene in RH, capable of interacting with multiple allelic variants of the pistil-specific S-ribonucleases (S-RNases). Further, Sli gene functions like a general S-RNase inhibitor, to impart SC to RH and other self-incompatible potatoes. Discovery of Sli now offers a path forward for the diploid hybrid breeding program.